2018
DOI: 10.1002/hep.30226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alcohol Consumption on Survival in Nonalcoholic Fatty Liver Disease: A National Prospective Cohort Study

Abstract: Nonalcoholic fatty liver disease (NAFLD) comprises more than two thirds of patients with chronic liver disease in the United States. The effect of alcohol consumption on survival in patients with NAFLD is not clear. We gathered data on National Health and Nutrition Examination Survey participants from 1988 to 2010, and linked them to the National Death Index for follow-up of their survival. We diagnosed NAFLD based on a previously validated biochemical model (Hepatic Steatosis Index). We built multivariate Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
70
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 52 publications
4
70
0
3
Order By: Relevance
“…A recent study based on the US population with 4,568 subjects with NAFLD (defined by the hepatic steatosis index) found reduced mortality among subjects consuming 0.5‐1.5 alcoholic drinks/day, whereas >1.5 drinks/day became harmful, thus reinforcing a J‐shaped association …”
Section: Discussionmentioning
confidence: 99%
“…A recent study based on the US population with 4,568 subjects with NAFLD (defined by the hepatic steatosis index) found reduced mortality among subjects consuming 0.5‐1.5 alcoholic drinks/day, whereas >1.5 drinks/day became harmful, thus reinforcing a J‐shaped association …”
Section: Discussionmentioning
confidence: 99%
“…12 After further adjustment for diabetes and general/abdominal obesity, the association was attenuated and remained significant suggesting that the link between depression and NAFLD is partly mediated by diabetes and obesity. [23][24][25][26][27][28][29]44,45 However, prospective studies using imaging or histology are needed to reproduce and reconfirm these observations in future. 43 When we further adjusted for insulin resistance, the association was attenuated and remained significant suggesting that the association between depression and NAFLD may be partly mediated by insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…44 Recently, Hajifathalian et al presented data from the National Health and Nutrition Examination (NHANES) survey, that modest alcohol consumption of less than 1.5 drinks of alcohol per day is associated with decreased risk of overall mortality in persons with biochemically-assessed NAFLD (HR 0.64, CI 0.42–0.97, p=0.035). 45 However, the authors also found that drinking more than 1.5 drinks of alcohol per day was actually linked to an increased hazard of death (HR 1.45, CI 1.01–2.19, p=0.047). 45 Thus, the potential “therapeutic window” for the beneficial effect of alcohol use in NAFLD appears very narrow limiting the safely profile for a clinical recommendation of moderate alcohol use as a preventive measure to reduce morbidity and mortality in NAFLD.…”
Section: Discussionmentioning
confidence: 95%
“…45 However, the authors also found that drinking more than 1.5 drinks of alcohol per day was actually linked to an increased hazard of death (HR 1.45, CI 1.01–2.19, p=0.047). 45 Thus, the potential “therapeutic window” for the beneficial effect of alcohol use in NAFLD appears very narrow limiting the safely profile for a clinical recommendation of moderate alcohol use as a preventive measure to reduce morbidity and mortality in NAFLD. Importantly, cause of death was not reported in this study and the authors did not account for interactions between race and sex by alcohol consumption.…”
Section: Discussionmentioning
confidence: 95%